Paisajes tópicos. Del lugar común a los lugares comunes en la fotografía contemporánea (chilena) - Goffard, Nathalie (CIICLA, Universidad de Costa Rica, 2018)
The aim of this essay is to speculate on the semantic correspondences between the notions of “place” and “common place” engaging landscape photography as a common thread. Specifically, it is exposed that the changes of aesthetic paradigms in contemporary photography are reactive and dialogue with the other social uses of photography, and in this case tourism. Furthermore it suggests that these relationships have become more complex in a context of greater commercialization and patrimonialization of the landscape, leading artists to prefer to represent banal places. In this line, the idea of stereotyped photography of typical landscape is suggested to analogy with the figure of the commonplace, to formulate the hypothesis of how visual overproduction affects the renewal of the landscape imaginary. In sum, this relationship is problematized in the context of the Chilean visual arts to conclude, that the landscape is first and foremost a dynamic cultural artefact that varies complain the becoming beside the point of view.